Detecting the QCD phase transition in the next Galactic supernova neutrino burst - Dasgupta, Basudeb; Fischer, Tobias; Horiuchi, Shunsaku; Liebendörfer, Matthias; Mirizzi, Alessandro; Sagert, Irina; Schaffner-Bielich, Jürgen (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
Predictions of the thermodynamic conditions for phase transitions at high baryon densities and large chemical potentials are currently uncertain and largely phenomenological. Neutrino observations of core-collapse supernovae can be used to constrain the situation. Recent simulations of stellar core collapse that include a description of quark matter predict a sharp burst of ¯νe several hundred milliseconds after the prompt νe neutronization burst. We study the observational signatures of that ¯νe burst at current neutrino detectors—IceCube and Super-Kamiokande. For a Galactic core-collapse supernova, we find that signatures of the QCD phase transition can be detected, regardless of the neutrino oscillation scenario. The detection would constitute strong evidence of a phase transition in the stellar core, with implications for the equation of state at high matter density and the supernova explosion mechanism.